The Concept of Human Dimension in the Context of Anthropological Discourse of Humanistic Management (Laisvalaikio tyrimai, 2018)
Grounding  of  research. Human dimension  comes  from  the  fact  that  reserves  of  humanistic  development  of  economics,  politics  and  culture  are  to  be  found  in  man  himself,  the  development  of  his  consciousness and spiritual capital. Without the development of anthropological capital, further development  and improvement of society become impossible. The most important resource of human dimension appears  intensification  of anthropological  capital  and  human  existence.  Anthropological  principles  of  human  dimension are terms of saving human, natural, social and political resources. In its substantive characteristics,  concept of human dimension includes theoretical and conceptual grounding of “ typical” tasks of humanization  of politics, economy, ecology, social policy, science, education and culture. Problem  situation.  In  the  context  of  philosophical  and  anthropological  dimensions,  emphasis  is shifted  to  human  ontology,  in  which  doctrine  of  the  meaning  of  human  life  and  the  possibilities  of  its comprehension, in particular by examining the conflict  of human world -attitude and self-creation is central.  Through  the  anthropological  principle,  an  attempt  to  explain  the  man  himself  and  the  surrounding  world, comprehend the man and the surrounding world, understand the man as a unique phenomenon, as the creator of history and culture is made. Fundamental questions of philosophical and anthropological discourse  – the attitude of man to the world and the world to man: What is the world we live in? What is man's place in this world? What is the man himself and what is the nature of his consciousness? Research  problems. Philosophical  and  anthropological  aspect  of  humanistic  management  is  fundamental in European philosophy, so we turn to the reception of man in the projection of anthropological  dimensions of hu man being, which are reduced to the following trends, existing in the world today. The aim of research : analyse The concept of the human dimension as  the anthropological basis of  humanistic management tasks. Conclusions. To  fulfil all  tasks  of  concept  of  human  dimension  as  the  anthropological  basis  of  humanistic  management,  it  is  necessary  to  form  the  elite  of  humanitarian  managers,  exercise  social  and  humanitarian policy by forming the key objectives of humanitarian management act ivity in human dimensional  direction:  a)  national  (semiotic);  b)  personal  growth  and  activity  self - determination  (anthropological);  c)spatial;  d)  strategic  thinking  and  political  action.  Promote  development  of  human  dimensional  outlook  of  humanitarian man agers and development of human dimensional technologies, which are a set of scientifically  grounded  methods  and  special  techniques  of  indirect  impact  on  society  through  the  management  of  social  human  behaviour. Promote modernization of human dimensional European space of Ukraine, which requires:  establishing a modern human dimensional culture of public management; full integration of Ukraine into the  information space; strengthening the Ukraine's presence in the global humanitarian space.Keywords: human dimension, anthropological discourse, humanistic management.